2016
DOI: 10.1136/sextrans-2016-052718.1
|View full text |Cite
|
Sign up to set email alerts
|

O001 Digital Sex and the City: Prevalent use of dating apps amongst heterosexual attendees of genito-urinary medicine (GUM) clinics: Abstract O001 Table 1

Abstract: Background/introductionStudies show that use of dating apps amongst men who have sex with men (MSM) is associated with an increased risk of sexually transmitted infections (STIs), including HIV. There is a paucity of research regarding the use of similar apps amongst the heterosexual population.Aim(s)/objectivesTo quantify heterosexual use of dating apps and explore the sexual practices of app users.MethodsAnonymised questionnaires were offered to heterosexual attendees of two GUM clinics, throughout August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the one hand, some studies find a relationship between being a user of dating apps and performing more risky sexual behaviors (e.g., having more sexual partners, less condom use, more relationships under the effects of alcohol and other drugs), both among men from sexual minorities [ 19 ] and among heterosexual individuals [ 32 , 41 , 62 ]. On the other hand, some research has found that, although app users perform more risky behaviors, especially having more partners, they also engage in more prevention behaviors (e.g., more sex counseling, more HIV tests, more treatment) and they do not use the condoms less than non-users [ 18 , 50 , 64 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, some studies find a relationship between being a user of dating apps and performing more risky sexual behaviors (e.g., having more sexual partners, less condom use, more relationships under the effects of alcohol and other drugs), both among men from sexual minorities [ 19 ] and among heterosexual individuals [ 32 , 41 , 62 ]. On the other hand, some research has found that, although app users perform more risky behaviors, especially having more partners, they also engage in more prevention behaviors (e.g., more sex counseling, more HIV tests, more treatment) and they do not use the condoms less than non-users [ 18 , 50 , 64 , 79 ].…”
Section: Resultsmentioning
confidence: 99%